Analisis Stratifikasi dan Klasifikasi Tanah dengan Variasi Metode Grafik pada Uji CPT (Cone Penetration Test) - Saputra, Hendra (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Soil investigation is an important phase in geotechnical engineering design and planning, as it determines soil stratification and technical characteristics. This study investigates the classification of soils in Indonesia using the Cone Penetration Test (CPT) and several interpretation approaches. The investigation employed graphs of the association between conus resistance (qc), local shear resistance (fs), and shear banding number (Rf), with changes based on recent research. The study was carried out at eight separate locations to a depth of 25 meters in Cikidang Village, West Java. At a depth of 0 to 15 meters, the findings graphically demonstrate the domination of clay with a firm to very stiff consistency, and at a depth of 15 to 25 meters, the dominance of sand. The Terzaghi and Lunne techniques define soil as silt. This variation in interpretation necessitates comparing the results of additional tests. Furthermore, the test equipment in these procedures does not include CPTs or manual sondirs, which are widespread in Indonesia. The findings are intended to improve understanding of soil classification and serve as a valuable reference for foundation design and planning in Indonesia.